Structural Regulation and Selective Catalysis of Biomass-Derived Carbon-Based Non-Precious Metal Nanocatalysts - Liu, Yifan; Yang, Yong (Synlett, 2025)
In this account, we summarize our recent progress on the structural regulation and selective catalysis of biomass-derived carbon-based non-precious nanocatalysts (Fe, Co, Ni, and Cu) in organic reactions that include the selective hydrogenation of functional nitro compounds to amines, selective oxidation of alkenes, selective coupling reactions, and selective hydrogenation of unsaturated aldehydes.1 Introduction2 Fe-Based Catalysts3 Co-Based Catalysts4 Ni-Based Catalysts5 Cu-Based Catalysts6 Conclusions
Keywords: biomass-derived carbon; carbon-based nanocatalyst; non-precious metal; selective catalysis; structural regulation